Customer Satisfaction as an Influence Mediation of Service Quality, Financial Considerations, Convenience Toward Switching Behavior (Study on Customer of PT. Bank Central Asia Tbk, Branch Malang) - Kanti Rahayu; Rofiaty Rofiaty; Sudjatno Sudjatno (Wacana Journal of Social and Humanity Studies, 2017)
This research has discussed switching behavior problem mediated by customer satisfaction. The aims of this research are to understand customer satisfaction dimension which are consist of service quality, financial considerations, and convenience in its influence towards switching behavior, by using survey of 200 inactive customer to verify research hypothesis. Data analysis using Partial Least Square (PLS) analysis methods toward customer of PT. Bank Central Asia, Tbk branch Malang. This result research has shown that service quality significantly influence to switching behavior financial consideration significantly influence to switching behavior in term of low savings rate dimension, but insignificant to administration fee and loan interest, convenience insignificantly influence to switching behavior in terms of ATM and service hours. New findings that convenience is also involve provided parking lot, almost in every branch office of BCA in Malang complaining the same thing.